Hygienisation, Gentrification, and Urban Displacement in Brazil - Garmany, Jeff; Richmond, Matthew A. [UNESP] (Wiley-Blackwell, 2019)
This article engages recent debates over gentrification and urban displacement in the global South. While researchers increasingly suggest that gentrification is becoming widespread in Southern cities, others argue that such analyses overlook important differences in empirical context and privilege EuroAmerican theoretical frameworks. To respond to this debate, in this article, we outline the concept of higienizacao (hygienisation), arguing that it captures important contextual factors missed by gentrification. Hygienisation is a Brazilian term that describes a particular form of urban displacement, and is directly informed by legacies of colonialism, racial and class stigma, informality, and state violence. Our objective is to show how Southern concepts like hygienisation help urban researchers gain better insight into processes of urban displacement, while also responding to recent calls to decentre and provincialise urban theory.
Keywords: gentrification; urban displacement; postcolonial theory; global South; urban theory; Latin America